Hubungan Body Image Terhadap Kecemasan Sosial Pada Remaja Putri di SMK Negeri 1 Ngawi - Destresa Nurul Rahmanda; Evi Yunita Nugrahini; Domas Nurchandra Pramudianti; Klanting Kasiati (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Adolescence is a transition period from childhood to adulthood. In 2020, 15.8% of Indonesian teenagers suffered from social anxiety. In 2020 in Ngawi Regency, 93.18% of teenagers aged 18-25 years experienced mild anxiety. This type of research is Observational Analytical, with a cross sectional design. The population was 140 female students and the sample was 104 female students. The independent variable is body image, the dependent variable is Social Anxiety. Body image was measured using the BSQ-16, anxiety levels were measured using the ZSAS questionnaire. Spearman Rank data analysis. Characteristics of respondents aged 15-17 years with 2-4 types of social media. Most have a positive body image and do not have social anxiety. The research results obtained a significant p-value of 0.000, meaning. There is a relationship between body image and social anxiety in young women at SMK Negeri 1 Sine. Based on this description, it can be concluded that someone who has a positive body image is not at risk of experiencing social anxiety. It is hoped that educators will be able to provide counseling and education regarding social anxiety in adolescents in order to increase female students' self-confidence.